Physiological correlates of golf performance - Wells, G. D.; Elmi, M.; Thomas, S. (The Journal of Strength and Conditioning Research, 2009)
Golf is now a sport where physical training is an integral component of elite players' practice and contributes to the ability to play at a high level consistently and without injury. Relationships between physical conditioning and golf performance have not been reported. Therefore, the objective of this research was to identify physiological correlates of golf performance in elite golfers under laboratory (ball speed and distance) and tournament conditions (average score, greens in regulation, short game measures, and putting accuracy). The correlation analysis revealed significant associations between mass, height, body mass index, sit height, arm length, and predicted Vo2max and golf measures. Significant correlations were noted between anterior abdominal muscle endurance and driver carry distance (r = 0.38; P = 0.04) and average putt distance after a chip shot (r = -0.44; P = 0.03), between dominant side abdominal muscle endurance and average putt distance after a chip shot (r = -0.43; P = 0.03), and between nondominant-side abdominal muscle endurance and average putt distance after a sand shot (r = -0.59; P = 0.001). Further correlations were found among sit and reach and driver carry distance (r = -0.36; P = 0.04), 5-iron ball speed (r = - 0.41; P = 0.02), 5-iron carry distance (r = -0.44; P = 0.01), and score (r = 0.43; P = 0.03). Correlation analysis revealed significant associations among peripheral muscle test results, golf driver results, 5-iron ball measures, score, and putting efficacy. These results may be important for developing training programs based on sound physiological rationale and for the development of talent identification programs. Results suggest that core strength and stability, flexibility, balance, and peripheral muscle strength are correlated with golf performance and should be included in golf training programs.